1977
DOI: 10.1002/apmc.1977.050600103
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between rheology, morphology and physical properties in heterogeneous blends

Abstract: The morphology of heterogeneous blends of polybutadiene (PBD) and EPDM was selectively varied by a change of either the rheology of the blend components during mixing or of the blend composition. Under a given set of mixing conditions, the blend system approaches a "steady state morphology", which was found to be relatively independent of sample history. However, during subsequent compression molding, the morphology of the sample may be altered substantially with phase inversion occurring in some cases. A mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…Several relationships have been proposed for estimating the phase‐inversion point based on the torque ratio6–8 or viscosity ratio of the blend components,9, 10 According to these theories and empirical relationships, when the viscosities of the blend components are unequal, the low‐viscosity component encapsulates the high‐viscosity component and becomes the continuous phase. All these theories predict that the cocontinuous morphology is reached at only one certain value of composition.…”
Section: Introductionmentioning
confidence: 99%
“…Several relationships have been proposed for estimating the phase‐inversion point based on the torque ratio6–8 or viscosity ratio of the blend components,9, 10 According to these theories and empirical relationships, when the viscosities of the blend components are unequal, the low‐viscosity component encapsulates the high‐viscosity component and becomes the continuous phase. All these theories predict that the cocontinuous morphology is reached at only one certain value of composition.…”
Section: Introductionmentioning
confidence: 99%
“…In the range 40/60 to 60/40, there are usually co continuous phases. However, material variables such as the interfacial tension and viscosity ratio strongly influence the morphology of the blend [90][91][92][93][94]. Danesi and Porter [90], studying (polypropylene/ethylene propylene rubber) blends, found that finer dispersions were obtained when the minor phase had an equal or lower viscosity than the major phase.…”
Section: Observations On Mechanically Mixed Polymer Blendsmentioning
confidence: 99%
“…This is a well-known phenomenon with a low-viscosity liquid such as combinations of oil in water or in salad dressings. There is a long history of investigations of coalescence in polymer melt blends, especially under quasi-quiescent conditions [60,92,[94][95][96][97]. The rate of coalescence of dispersed phases is increased by large interfacial tensions, small droplet size, anisotropic droplet shape, and quiescent low deformation rate conditions.…”
Section: Coalescencementioning
confidence: 99%
“…This procedure has been reported to be a good tool for determining the cocontinuous region and phase inversion in heterogeneous polymer blends. [40][41][42] A cocontinuous structure is assumed when the complete NBR phase can be extracted and the specimen still maintains its dimensional stability. The weight of the specimen after the extraction corresponds to the weight fraction of the EPDM component.…”
Section: Morphological Aspectsmentioning
confidence: 99%
“…[40][41][42] The torque values of the EPDM and NBR components correspond to 27 Nm and 17 Nm, respectively. [39] From the torque ratio, one can estimate the phase inversion point at a NBR/EPDM ¼ 39:61 vol.-%.…”
Section: Morphological Aspectsmentioning
confidence: 99%